2001
DOI: 10.1046/j.1365-2222.2001.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective protective effects of nitric oxide inhalation on allergen‐induced acute airway reactions in the pig

Abstract: These findings indicate that NO inhalation improves ventilation/perfusion matching and causes some bronchodilatation during the allergen-induced acute airway reaction, whereas histamine release is not affected. Moreover, NO inhalation enhanced the clearance of extravasated protein in the airways, possibly through increased bronchial blood flow. Even though some protective effects were seen, this study does not support a therapeutic role for exogenous NO in acute allergic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We also saw a very modest hepatic neutrophilia in the I/R injury animals, but G31P had no significant effect on this response. While we found no airway neutrophilia in our I/R injury animals, we did find evidence of increased vascular leakage, as determined using BAL fluid protein levels as a surrogate marker [28]. Airway protein levels and RBC numbers were increased at the 5 h time-point (Fig.…”
Section: The Impact Of Elr-cxc Chemokine Antagonism On Local and Remomentioning
confidence: 57%
“…We also saw a very modest hepatic neutrophilia in the I/R injury animals, but G31P had no significant effect on this response. While we found no airway neutrophilia in our I/R injury animals, we did find evidence of increased vascular leakage, as determined using BAL fluid protein levels as a surrogate marker [28]. Airway protein levels and RBC numbers were increased at the 5 h time-point (Fig.…”
Section: The Impact Of Elr-cxc Chemokine Antagonism On Local and Remomentioning
confidence: 57%
“…Interest has mainly been in deposition and targeted delivery of aerosols and gas [6,28,29]. For instance, it has been shown that NO has caused bronchodilation and improved ventilation [30,31]. It should be pointed out that in general there is a Reynolds number difference between the airway and the arterial system.…”
Section: Introductionmentioning
confidence: 99%